2013
DOI: 10.1136/bmjopen-2013-002640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health confidence in rural, suburban and urban areas in the UK and the USA: a secondary analysis

Abstract: ObjectiveConfidence in healthcare may influence the patients’ utilisation of healthcare resources and perceptions of healthcare quality. We sought to determine whether self-reported confidence in healthcare differed between the UK and the USA, as well as by rurality or urbanicity.DesignA secondary analysis of a subset of survey questions regarding self-reported confidence in healthcare from the 2010 Commonwealth Fund International Health Policy Survey.SettingTelephone survey of participants from the UK and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…rural or urban area). [4][5][6][7][8] Public trust in the government has also been shown to be related to trust in the health care system. 9,10 Empirical evidence on public trust in health care systems in low-and middle-income countries (LMIC) has been limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…rural or urban area). [4][5][6][7][8] Public trust in the government has also been shown to be related to trust in the health care system. 9,10 Empirical evidence on public trust in health care systems in low-and middle-income countries (LMIC) has been limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, a multinational study with 31 countries showed opposite results; people living in urban areas showed lower trust in the health system [ 19 ]. Results have been observed in China that are similar to the case of northern Sweden, while no differences between urban and rural areas were reported in the UK [ 23 , 28 ]. Our results are probably context specific to northern Sweden where there are smaller rural municipalities with no hospitals and relatively long distances from healthcare facilities, and where rural citizens experiencing a policy of abandonment by central authorities.…”
Section: Discussionmentioning
confidence: 63%
“…Although not specifically studied in suicide-bereaved populations, Haven et al. investigated health confidence in rural, suburban and urban areas in the general population in the US ( n = 2,501) and the UK ( n = 1,511; Haven, Celaya, Pierson, Weisskopf, & Mackinnon, 2013). Health confidence was measured by asking the participants about their confidence in receiving effective treatment and confidence in being able to afford the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we found no difference between bereaved parents living with a partner and bereaved parents who were widows/widowers. Probably, in conjunction with having raised a psychologically vulnerable child alone, bereaved single parents may have experienced additional stressors such as economic disadvan- Celaya, Pierson, Weisskopf, & Mackinnon, 2013). Health confidence was measured by asking the participants about their confidence in receiving effective treatment and confidence in being able to afford the treatment.…”
Section: Discussionmentioning
confidence: 99%